2009
DOI: 10.3174/ajnr.a1530
|View full text |Cite
|
Sign up to set email alerts
|

A Second-Generation, Endoluminal, Flow-Disrupting Device for Treatment of Saccular Aneurysms

Abstract: BACKGROUND AND PURPOSE:We report a preclinical study of a second-generation endoluminal device (Pipeline Embolization Device [PED-2] for aneurysmal occlusion and compare the PED-2 with its first-generation predecessor (PED-1).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
125
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 186 publications
(130 citation statements)
references
References 14 publications
3
125
1
1
Order By: Relevance
“…10 Previous clinical, animal, and computational studies have examined the propensity for branch artery occlusion following flow-diversion implantation. 5,6,11,12 Kallmes et al 13,14 found that on occlusion of lumbar branch vessels in the rabbit aorta with overlapping flow-diversion devices, these perforating vessels remained patent on follow-up. While a device placed across the origin of a perforating vessel (traditionally considered end vessels with no distal collaterals) may maintain flow across the ostium due to a pressure gradient across its ostium, the same is not true when larger vessels like the ophthalmic artery and the posterior communicating artery (which often have significant distal collateral potential) are covered by these devices.…”
Section: Discussionmentioning
confidence: 99%
“…10 Previous clinical, animal, and computational studies have examined the propensity for branch artery occlusion following flow-diversion implantation. 5,6,11,12 Kallmes et al 13,14 found that on occlusion of lumbar branch vessels in the rabbit aorta with overlapping flow-diversion devices, these perforating vessels remained patent on follow-up. While a device placed across the origin of a perforating vessel (traditionally considered end vessels with no distal collaterals) may maintain flow across the ostium due to a pressure gradient across its ostium, the same is not true when larger vessels like the ophthalmic artery and the posterior communicating artery (which often have significant distal collateral potential) are covered by these devices.…”
Section: Discussionmentioning
confidence: 99%
“…These are presumably associated with hemodynamic and not embolic factors. Recent studies, both in animals 11,12 and in clinical practice, 19 suggest that in the case of laminar flow, due to a high pressure gradient in the covered side branch, the side branch remains patent, even with multiple overlapping devices. 8 Thus, in cases in which an important collateral network exists or develops, a "competition" of flow may have as a result a decrease in pressure gradient between the covered ostium and the distal portion of the arterial branch, contributing in such a way to a hemodynamic "stagnation.…”
Section: Supplementary Comparison With the Department's Series Of Stementioning
confidence: 99%
“…3,12,14,15,19 A flow diverter is a braided stent consisting of a thick, flexible, tubular mesh. Because of its mechanical properties, when a flow diverter is deployed at the level of an aneurysm neck, it causes stagnation of blood, thus promoting thrombosis of the aneurysm sac while providing scaffolding for endothelialization.…”
mentioning
confidence: 99%
“…[8][9][10][11][12] Unlike current endoluminal flow-diversion devices, the Luna AES does not require the use of dual antiplatelet therapy. Furthermore, at least on the basis of the preclinical work described here, the Luna AES might also achieve immediate or nearly immediate cessation of flow within the aneurysm cavity due to a high degree of neck coverage compared with coiling, allowing its use in ruptured aneurysms.…”
Section: Discussionmentioning
confidence: 99%
“…However, flow diverters have had limited clinical utility, though they have shown excellent occlusion rates, even in large and giant aneurysms. [8][9][10][11][12] These devices may remain problematic in ruptured aneurysms, not only because they require concomitant use of dual antiplatelet therapy but also because immediate aneurysm occlusion usually does not occur. Furthermore, there are drawbacks when placing these devices in bifurcation aneurysms due to the inherent design limitations.…”
mentioning
confidence: 99%